2019
DOI: 10.1002/jee.20301
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and engineering formation

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 54 publications
4
66
0
3
Order By: Relevance
“…As evidenced by so many students who indicated dissatisfaction with virtual communication effectiveness, faculty should explore how empathy factors into such interactions. Empathy includes perceiving others' feelings, behaviors, and motivations [44], and it is vital to successful team performance [45]. Walther et al argued that empathy-building needs to be included explicitly in engineering courses.…”
Section: Consider the Importance Of Empathymentioning
confidence: 99%
“…As evidenced by so many students who indicated dissatisfaction with virtual communication effectiveness, faculty should explore how empathy factors into such interactions. Empathy includes perceiving others' feelings, behaviors, and motivations [44], and it is vital to successful team performance [45]. Walther et al argued that empathy-building needs to be included explicitly in engineering courses.…”
Section: Consider the Importance Of Empathymentioning
confidence: 99%
“…Today, this can be accomplished with the help of outlines and schemas prepared with computing programs [15]. Some authors stress also the need to take the gender perspective into consideration [22,23].…”
Section: The Written Skills In Engineering Educationmentioning
confidence: 99%
“…In the third module, students focused on responding and mirroring conversation partners (a skill exercise) and role-played stakeholders in an advisory committee (an applied exercise). Qualitative analysis of students' reflections revealed that the course helped students to consider the elements of power, distance, and difference between engineers and community stakeholders [65]. Some challenges students encountered included immersing themselves within fictional role-playing scenarios and initiating conversations with other students.…”
Section: Teaching Empathy In Undergraduate Engineeringmentioning
confidence: 99%